Refractive status and ocular characteristics of preschool children with retinopathy of prematurity after different treatments - Wu-Yang Jiang; Man-Hong Li; Hao Wang; Dong Niu; Yu-Sheng Wang; Zi-Feng Zhang (International Journal of Ophthalmology)
AIM: To compare the changes in preschool refractive status, ocular biological parameters, and higher-order aberrations in children with retinopathy of prematurity (ROP) after retinal laser photocoagulation or anti-vascular endothelial growth factor (anti-VEGF) treatment and explore their underlying factors. METHODS: This observational study involved 118 eyes of 59 children, aged 3 to 6y, with ROP followed up between March 2023 and October 2024. They were divided into the laser, anti-VEGF, and anti-VEGF+laser groups. The laser group received a single session of laser photocoagulation. The anti-VEGF group received a single anti-VEGF treatment. The anti-VEGF+laser group received a single anti-VEGF treatment after birth followed by supplementary laser treatment within 2wk to 6mo. Ocular biological parameters were measured using IOL Master 700 and Pentacam HR. Right-eye higher-order aberrations were measured using the OPD-Scan III. Best-corrected visual acuities (BCVA), refractive statuses, ocular biological parameters, and higher-order aberrations were assessed and compared. Multiple linear regression analysis was conducted to evaluate the relationships among ocular biological parameters, higher-order aberrations, spherical equivalent (SE), and treatment methods. Pearson's correlation coefficients were used to assess the relationships between the SE and higher-order aberrations. RESULTS: The laser group had a higher incidence of myopia and a lower SE than the anti-VEGF group. The incidence of astigmatism and cylindrical power were significantly lower for the anti-VEGF than for the laser and anti-VEGF+laser groups (P<0.05). The anterior corneal surface astigmatism was higher for the laser and anti-VEGF+laser groups than for the anti-VEGF group. The anterior corneal surface K2 and lens thickness were higher for the laser and anti-VEGF+laser groups than for the anti-VEGF group. The whole-eye higher-order aberration root mean square (RMS) values for the right eye were significantly higher for the laser and anti-VEGF+laser groups than for the anti-VEGF group. The whole-eye trefoil RMS values for the right eye were also significantly higher for the laser and anti-VEGF+laser groups than for the anti-VEGF group (P<0.05). Laser treatment was significantly associated with SE, anterior corneal surface curvature and astigmatism, lens thickness, whole-eye high-order aberrations, and whole-eye trefoil (all P<0.05). CONCLUSION: Children with ROP who received laser treatment have higher myopia and astigmatism than those who received anti-VEGF treatment. Children treated with laser or supplementary laser treatment have higher anterior corneal astigmatism, anterior corneal curvature, thicker lenses, whole-eye higher-order aberrations, and whole-eye trefoil. The cause of myopia in children with ROP after laser treatment is increased anterior corneal surface curvature and lens thickness.